Cover Feature: Effect of "X" Ligands on the Photocatalytic Reduction of CO2 to CO with Re(pyridylNHC‐CF3)(CO)3X Complexes (Eur. J. Inorg. Chem. 19/2020). Issue 19 (6th May 2020) - Shirley, Hunter; Sexton, Thomas More; Liyanage, Nalaka P.; Palmer, C. Zachary; McNamara, Louis E.; Hammer, Nathan I.; Tschumper, Gregory S.; Delcamp, Jared H.
Abstract : The Cover Feature shows the impact of an "X" ligand on the performance of photocatalysts reducing CO2 to CO via a series of pyridyl N‐heterocyclic carbene rhenium tricarbonyl complexes. These catalysts show impressive rate and durability in this reaction upon judicious "X" ligand selection. An in‐depth look into the theoretical dissociation energies and photophysical properties of these ligands has led to a promising method for predicting rate and durability metrics in the CO2 reduction reaction for these pyridyl NHC systems, with the potential to expand this analysis to other ligand frameworks and metals. More information can be found in the Full Paper by J. H. Delcamp et al.